Comparison of Combination of TOGA and Basalt Feed as Immunomodulator ln Male Chickens (Agrikan Jurnal Agribisnis Perikanan, 2021)
The purpose of this study was to compare the results between the addition of TOGA combination in feed as an immunomodulator in male chickens. The research method used Factorial Design with 2 treatments namely: P1 treatment (basal feed) and P2 treatment (basal feed mixed with TOGA flour combination). The test animals used 40 roosters with an average weight of 50 g. Each treatment consisted of 20 chickens divided into two groups of 10 chickens each and performed for 30 days. Data analysis using Variety Imprint Test and Least Real Difference Test (BNT). Daily growth (DG) results P1 12.1%> P2 11%. Absolute growth (W) P1 363 g> P2 330 g. Feed consumption (FI) P1 6713.1 g> P2 6636.8 g. Mortality (D) P1 0.15 %> P2 0.0 %. Conclusions from the research results of basal feed can accelerate the growth of chickens, while the combination of TOGA is able to maintain 0 % survival compared to basal feed by 0.15 %. The benefits of giving a combination of TOGA mixed with feed are thought to be a natural immunomodulator for roosters
Keywords: Ayam Pejantan; TOGA; imunomodulator